Elucidation of the electron transfer environment in the MMOR FAD-binding domain from Methylosinus sporium 5. Issue 45 (4th November 2021) - Lee, Chaemin; Ha, Sung Chul; Rao, Zhili; Hwang, Yunha; Kim, Da Som; Kim, So Young; Yoo, Heeseon; Yoon, Chungwoon; Na, Jeong-Geol; Park, Jung Hee; Lee, Seung Jae
Abstract : Biophysical studies of MMOR–FAD demonstrate that Tyr160 is a key regulator for electron transfer. Abstract : By facilitating electron transfer to the hydroxylase diiron center, MMOR—a reductase—serves as an essential component of the catalytic cycle of soluble methane monooxygenase. Here, the X-ray structure analysis of the FAD-binding domain of MMOR identified crucial residues and its influence on the catalytic cycle.